Give Them a Chance: Public Attitudes to Sentencing Young Offenders in Western Australia. (August 2018) - Ellis, Suzanne; Gately, Natalie; Rogers, Shane; Horrigan, Andrée
Public opinion is often reported as punitive towards sentencing young people. Attitudes remain important to investigate given their potential to influence policy within the criminal justice system. Therefore, it is important to understand the formation of these attitudes and their consistency with sentencing principles. Semi-structured interviews ( n = 72) and surveys ( n = 502) were used to gauge opinions of sentencing young people under different scenario manipulations (age, weapon, drug treatment, prior record). The findings revealed the public expected punishment, but favoured rehabilitation with an opportunity to repent, suggesting the public are open to alternatives to 'tough on crime' approaches.